Hubungan Kualitas Tidur Dengan Kadar Eritrosit Pada Pekerja Sistem Shift - Aristoteles Aristoteles; Nurhidayanti Nurhidayanti (Universitas PGRI Palembang, 2022)
Everyone needs to know the condition of the body that can restore the body's stamina so that the optimal condition is the need for sleep. Working hours and biological rhythms that do not match can cause stress in the form of hormonal changes that are controlled by the hypothalamus. The hypothalamus will trigger the anterior pituitary to increase cortisol. Cortisol reduces the number of eosinophils, basophils, monocytes, and lymphocytes, interleukins 1 and 6 as well as suppression of T cells in the blood so that the level of immunity against foreign substances entering the body is reduced. The purpose of this study was to determine the effect of sleep quality on the formation of erythrocytes in workers with a shift system in the peripheral circulation. This study uses analytical estimation through a horizontal approach. Based on the analysis, there is a significant relationship between sleep quality and the number of ATLM episodes with the shift work system at BBLK Palembang. Chi Square statistical test results obtained from 86 people there are 35 people with good sleep quality, from 35 respondents with good sleep quality 33 people (94.3%) have a good blood count and 2 respondents (5.7%) others have a low blood cell count. As for ATLM with a shift work system, it is expected to be able to maintain good and sufficient sleep quality, as well as improve good sleep quality.